Weighted \(G^0\)- and \(G^1\)-Degree Reduction of Disk Bezier Curves - Rababah, Abdalah; Hamza, Yusuf Fatihu (Journal of Informatics and Mathematical Sciences, 2016)
A Bezier curve in the plane whose control points are disks is called a disk Bezier curve. In this paper we introduce a novel approach to find weighted degree reduction of disk Bezier curve with \(G^0\)- and \(G^1\) continuity at the boundary. Numerical examples are provided to demonstrate the efficiency and simplicity of the proposed method. Moreover some figures are provided to illustrate the comparisons with other methods.